Cancer of the nose and paranasal sinuses in the metal industry: a case-control study. Issue 3 (March 1992) - Comba, P; Barbieri, P G; Battista, G; Belli, S; Ponterio, F; Zanetti, D; Axelson, O
Abstract : The association between nasal cancer and work in the metal industry was investigated in a case-control study located in the province of Brescia, north eastern Italy. Thirty five cases of malignant epithelial neoplasms of the nasal cavity and paranasal sinuses who were resident in the province of Brescia and diagnosed or treated by the ear, nose, and throat department and the radiotherapy unit (Centro Alte Energie) of the Brescia Hospital in the years 1980-9 were included in the study. Controls (102) were patients affected by benign and malignant neoplasms of the head and neck who were resident in the Brescia Province and matched the cases by age and sex. All the subjects were interviewed by telephone. Metal workers showed an increased risk of nasal cancer (odds ratio (OR) 3.1; 90% confidence interval (90% CI) 0.48-20); a higher risk was associated with work in foundries (OR 5.9; 90 CI 0.77-46). Work in wood, leather, and textile industries was also associated with increased risk of nasal cancer.